Study of saving and investment pattern on sample farms households - M. Singh; R. S. Singh; K. P. Singh (Овощи России, 2021)
The saving and investment pattern of different forms sample group was studied during 2014-16 and it was observed that large farm holders were able to save higher income than small farmers while lowest income group had negative savings. In respect of investment on different fixed assets, irrigation was on first priority, followed by purchase of milch animals, farms buildings and investment in land and its improvement. Investment on working capital amongst different cash inputs, hired human labourer accounted highest share (29.44 per cent), followed by manure & fertilizers (22.33 per cent), hired power tractor (16.96 per cent), irrigation (13.61 per cent) and seeds (13.50 per cent) to total cash inputs. Marginal farmers could not invest for nonfarm physical capital because of no savings with them. Small and large farmers groups invested in all the items in which it was highest in working capital (61.28 to 61.84 per cent), followed by investment in fixed capital (14.41 to 16.84 per cent), financial capital (12-14 per cent) and non-farm capital (7-12 per cent). The highest investment was made on working capital (69.02 per cent) by sample farmers. Current income was found to be the main source of finance in all income groups which accounted for 49.70 to 94.79 per cent share of the total investment followed by savings which shared for 40.10 to 49.12 per cent in total investment.